제선공정 온실가스 저감을 위한 바이오매스 활용 대체 환원제 개발 - 김가언; Ga Eon Kim; 오한상; Han Sang Oh; 이종협; Jong Hyup Lee; 박영주; Young Joo Park; 이유빈; Yu Bin Lee; 권재홍; Jae Hong Kwon; et al. (대한금속·재료학회지, 61(3), 2023)
Technologies to reduce CO 2 emissions in the steel industry have been actively developed since the early 1990s in order to deal with global climate change. In particular, the utilization of various types of biomass including wood, bamboo, grass, food and agricultural by-product are being attempted as carbon neutral fuels in the blast furnace process. In this study, an alternative reducing agent for coke and pulverized coal using biomass was developed and the effect on blast furnace performance and CO 2 reduction was evaluated. The first investigation was whether a burden material made of torrefied biomass mixed with iron ore and coal (Iron-bearing Biomass Coke, IBC) could be used as a substitute for coke in the form of a carbonized briquette. In addition, a method of mixing torrefied biomass with pulverized coal (Bio-PC) to inject through tuyere in a blast furnace was examined. As a result, when coke was replaced with 10% of IBC, the reducibility of the sintered ore was improved in association with an increased CO gas utilization ratio, hence CO 2 emissions decreased by 2.3%. Furthermore, the combustion efficiency of Bio-PC mixed with 10% of torrefied biomass was improved by 13.2%, thus, the amount of CO 2 emissions was calculated to decrease by 4%. These results suggest that the possibility of using IBC and Bio-PC in blast furnaces, as they could effectively reduce CO 2 emissions in the ironmaking process. (Received 18 October, 2022; Accepted 27 December, 2022)